Chemical kinetics and promoted Co-immobilization for efficient catalytic carbonylation of ethylene oxide into methyl 3-hydroxypropionate - Luo, Jingjie; Liu, Pengcheng; Yang, Wenhao; Niu, Hongyu; Li, Shaojie; Liang, Changhai (Frontiers in Chemistry, 2022)
The carbonylative transformation of ethylene oxide into methyl 3-hydroxypropionate (3-HPM) was a key process for the production of 1,3-propanediol (1,3-PDO) that is currently viewed as one of the most promising monomers and intermediates in polyester and pharmaceuticals industry. In this work, a homogeneous reaction system using commercial CO2(CO)8 was first studied for the carbonylation of EO to 3-HPM. The catalytic behavior was related to the electronic environment of N on aromatic rings of ligands, where N with rich electron density induced a stronger coordination with Co center and higher EO transformation. A reaction order of 2.1 with respect to EO and 0.3 to CO was unraveled based on the kinetics study. The 3-HPM yield reached 91.2% at only 40 oC by CO2(CO)8 coordinated with 3-hydroxypyridine. However, Co-containing colloid was formed during the reaction, causing the tough separation and impossible recycling of samples. Concerning the sustainable utilization, Co particles immobilized on pre-treated CNT (Co/CNT-C) were designed via an in-situ reduced colloid method. It is remarkable that different from a conventional Co/CNT, Co/CNT-C was highly selective toward the transformation of EO to 3-HPM with a specific rate of 52.2 mmol∙g_Co^(-1)∙h^(-1), displaying a similar atomic efficiency to that of coordinated CO2(CO)8. It is also indispensable to note the cyclic utilization of Co/CNT-C only with facile separation after each reaction.